Urgensi Kode Etik Guru dalam Membentuk Karakter Siswa: Studi Pemikiran KH. Hasyim Asy’ari - Ahmad, adam ahmad syahrul alim (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2020)
K.H. Hasyim Asy'ari in formulating the teacher's code of ethics, he first looked at the teacher as a profession that was very sacred and loaded with values of worship. The task of the teacher is not only limited to the activity of providing teaching, but also to provide education in the real sense. Namely directing students to have noble character and personality and noble behavior in accordance with religious and ethical norms. This paper aims to examine the code of ethics of a teacher described by KH. Hasyim Ash'ari in Chapters 5 through 8 of the book of Adab al-‘Alim wa al-Muta’allim. Using library research methods by taking several discussion points related to the purpose of writing. And among the results of this study are: 1. The Adabul Book ‘Alim Wal Muta’allim is one of the monumental works of KH Hasyim Asy’ari who talks about morals for education practitioners. 2. The author can pull some of the main substances that the author classifies into 5 important points, namely: related to the nature of the teacher; teacher as a profession; basic concepts of teaching / educating; teaching / educating methods; and the progression of KH. Hasyim Asy'ari about the teacher's code of ethics. 3. Teacher code of conduct formulated by KH. Hasyim Asy'ari has a significant level of relevance, especially regarding efforts to realize the ideals and goals of national education. Keywords: Code of ethic, KH. Hasyim Asy’ari, Adabul Alim wal Mutaallim.